The Edinburgh dictionary of continental philosophy - Protevi, John, 1955- (Edinburgh University Press, 2005)
The first ever dictionary of continental philosophy to be published. With over 450 clearly written definitions and articles by an international team of specialists, this authoritative dictionary covers the thinkers, topics and technical terms associated with the many fields known as 'continental' philosophy'. Special care has been taken to explain the complex terminology of many continental thinkers. Researchers, students and professional philosophers alike will find the dictionary an invaluable reference tool. Key Features in-depth entries on major figures and topics over 190 shorter articles on other figures and topics over 250 items on technical terms used by continental thinkers, from abjection [Kristeva] to worldhood [Heidegger] coverage of related subjects that use continental terms and methods extensive cross-referencing, allowing readers to relate and pursue ideas in depth. Entries include: Major Figures and Topics: Deleuze, Derrida, Foucault, Hegel, Heidegger, Husserl, Irigaray, Kant, Nietzsche Epistemology, Feminism, German Idealism, Marxism, Phenomenology, Poststructuralism, Time, etc. Other figures and topics covered include: Adorno, Althusser, Arendt, Badiou, Barthes, Bergson, Butler, Haraway, Habermas, Kristeva, Merleau-Ponty, Sartre, Schelling, Schiller, Weber, Weil, Wittgenstein, Zizek, etc; African Philosophy, Cognitive Science, Death, Ecocriticism, Embodiment, Environmental Philosophy, Modernity, Philosophy of Nature, NeoThomism, Postcolonial Theory, Psychology, Race Theory, Sex / sexuality, Space, Speech Act Theory, Structuralism, Subject, 'Young Hegelians', etc.